Tackling COVID-19 in Nepal: Opportunities and Challenges - Marahatta, Sujan Babu; Paudel, Shishir (Journal of Karnali Academy of Health Sciences, 2020)
The COVID-19 pandemic has become a global challenge that has driven nations to take some extreme measures in an attempt to prevent outbreaks and save lives. The scientific communities are trying their best to understand the activities of SARS CoV-2 virus to target effective strategies against it. The whole world is trying its best to contain the infection, Nepal is no exception. Nepal underestimated the likelihood of the COVID 19 outbreak during early January however with the increasing case strong measures have been initiated. Nepal reported 2,099 confirmed cases with 266 recoveries and 8 deaths by June 2, 2020. The focus on social distancing and since the middle of March countrywide lockdown has been taken as a strategy to control the rate of infection but the challenge lies in its continuation. There is also a challenge in extension of testing and other public health intervention.